Introduction to engineering - Wright, Paul H. (New York : John Wiley and Sons, 1994)
This book is about: History of engineering; Definition of engineering; Learning and creative thought; The engineering approach to problem solving; Engineering communications; ...
Keywords: Engineering; Engineering